Caracterização Biofísica e Avaliação de Aptidão de Terra do Distrito de Chicualacuala, Província de Gaza, Moçambique - Vilanculos M; Mafalacusser J; Jalane O (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The current biophysical characterization work was carried out in the Chicualacuala district, as part of the IIAM-CCAFS collaborative project “Managing climate Related Risks to Improve Livelihood Resilience and Adaptive capacity in Agricultural Ecosystems in Southern Mozambique”. Its main objective was to identify, describe, classify and map the main land units and uses in the districts, and evaluate their current potential suitability for agriculture and livestock in order to make recommendations to promote the sustainable use of resources.